P2_6 The Power of Moonlight - Dangerfield, Kyle; Walton, Sam; Lewis, Elspeth; Byrne, Jamie (Physics Special Topics, 2017)
In this paper we investigate the concept of using the Moon as an energy producing Mega-structure, by covering its surface in solar panels. We find that the energy yield, in 28 days, from using modern-day solar panels is 5.327x10^16 J and that 815 identical structures would be required to meet the global energy usage of 2016 (5.656x 10^20J).